Out of sight, out of mind? : the impact of natural disasters on pregnancy outcomes - Emilia Simeonova (Center for Economic Studies and ifo Institute (CESifo), 2009)
The impact of global climate change on health is not well understood. Besides the direct channel of increasing temperatures, there is a potentially more harmful one: through an increase in extreme weather incidents. We offer the first evidence on the effect of natural disasters on pregnancy outcomes. Elevated stress levels associated with extreme events increase the probability of a preterm birth. Preterm infants are more likely to be of low birth weight and are at increased risk of health problems later, implying even larger long run societal costs. Results confirm that exposure to extreme events increases the risk of preterm births.
Keywords: I10; I12; Q54; 330; Naturkatastrophe; Schwangerschaft; Gesundheit; USA